Safety, acceptability, and adherence to a dolutegravir-based regimen among adults living with HIV at Kenyatta National Hospital - Mwanthi, Caroline Kaeni; Oyugi, Julius; Omosa-Manyonyi, Gloria; Mugendi, George A. (International Journal Of Community Medicine And Public Health, 2022)
Background: Dolutegravir-based therapy was rolled-out in Kenya in 2017 with limited safety studies in the country and Africa. This study sought to assess and profile the adverse drug reactions, acceptability, and adherence to the newly rolled out dolutegravir-based regimens among HIV patients attending Kenyatta National Hospital. Methods: This was a cross-sectional study conducted between November and December 2019 at Kenyatta national hospital comprehensive care clinic. Through systematic random sampling, a sample of 219 adult HIV patients on a dolutegravir-based antiretroviral regimen were recruited and interviewed for the experience of adverse drug reactions, adherence, and acceptance of the dolutegravir-based regimen using a researcher-administered questionnaire. Descriptive analysis was conducted using IBM SPSS V 21 software. The alpha was set at p≤0.005. Results: A-quarter of the patients (24.7%, n=54) reported experiencing drug-related adverse drug reactions. The most frequent adverse reaction was insomnia (24.1%, n=19), followed by headaches (19.0%, n=15) and skin reactions (13.9%, n=11). The least cited was vomiting (2.5%. n=2). Most (87.3%, n=69) of the adverse reactions were mild (grade 1 reactions), with very few (7.6%, n=6) of them being severe (toxicity grade 3). Only 2 (0.9%) of the reactions resulted in the dolutegravir-based regimen switch. Adherence was high (97.3%, n=213), and 90.4% (n=198) of patients reported to accept the new dolutegravir-based regimen. Conclusions: Adult patients living with HIV on a dolutegravir-based regimen experienced some adverse drug reactions; mostly mild and resolved without medical intervention. Generally, the regimen had an acceptable safety profile, and a high adherence rate was reported.